2020
DOI: 10.1093/eurpub/ckaa223
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant under the pressure of a pandemic: a large-scale longitudinal survey before and during the COVID-19 outbreak

Abstract: Background One of the groups that is most vulnerable to the COVID-19 pandemic is pregnant women. They cannot choose to refrain from care; they and their children are at risk of severe complications related to the virus; and they lose comfort and support as clinics prohibit their partners and as societal restrictions demand isolation from friends and relatives. It is urgent to study how this group is faring during the pandemic and we focus here on their health-related worries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
62
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 37 publications
10
62
0
3
Order By: Relevance
“…Among the limitations of the present study, we should first acknowledge that selection bias should be considered: only 1% of the background eligible population contributed data; the application cannot be used by women not able to communicate in Swedish, or those not owning a mobile smartphone (8%). Nonetheless, the present results are in line with another recent Swedish study with better representation (37). We cannot exclude a potential bias in the results due to the self-reported nature of the information gathered.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Among the limitations of the present study, we should first acknowledge that selection bias should be considered: only 1% of the background eligible population contributed data; the application cannot be used by women not able to communicate in Swedish, or those not owning a mobile smartphone (8%). Nonetheless, the present results are in line with another recent Swedish study with better representation (37). We cannot exclude a potential bias in the results due to the self-reported nature of the information gathered.…”
Section: Discussionsupporting
confidence: 94%
“…However, not all women provided comments and thus, we cannot conclude whether the expressed emotions were representative of all women; however, the present results are in line with recent studies. Specifically, consistent with our results, a previous Swedish study including a regional population-based cohort showed increased levels of health-related worry in pregnant women during the months of the pandemic (February-August 2020) (37), whereas other studies have also reported increased levels of anxiety and depression due to loss of supportive perinatal services and uncertainty about the novel coronavirus disease (38).…”
Section: Discussionsupporting
confidence: 92%
“…A large-scale longitudinal survey carried out in Sweden revealed that, at the beginning of the pandemic, pregnant women experienced a considerable increase in worries regarding their own health and that of their child. These worries persisted at higher levels than usual throughout the pandemic [ 70 ]. Such feelings may have contributed to the increase in terminations seen during the COVID-19 pandemic.…”
Section: Effect Of Covid-19 On Neonatal Outcomesmentioning
confidence: 99%
“…Two other studies found a rise in psychosocial problems in postnatal women associated with social distancing and restrictions in the UK and Italy (11,12). A Swedish longitudinal study of 6,941 pregnant women and their partners showed that pregnant women experienced a dramatic increase in health-related worries during the pandemic (13).…”
Section: Introductionmentioning
confidence: 99%